2005
DOI: 10.1021/jp0538159
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Compensation in the Oscillatory Bray Reaction

Abstract: The influence of temperature on the oscillatory frequency of the hydrogen peroxide-iodate ion reaction is found to be two-sided: (i) the period length decreases with increasing temperature in most of the instances studied, (ii) or in some cases an opposite change is observed. A temperature-independent period length (temperature compensation) is also discovered experimentally in a rather wide temperature interval at a narrow concentration range of reactants both in a batch configuration and under flow condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 20 publications
1
23
0
4
Order By: Relevance
“…Temperature compensation of the oscillation period, or the near-independence of the oscillation period on temperature, is observed at high currents and at lower temperatures. For comparison, the temperature coefficient of 7 Temperature coefficients between 0.67 and 1.80 were obtained by Rábai and co-workers 34 for the classic Bray reaction. Those experiments were carried out in batch, within a temperature interval of 10°C, and the q 10 values were found to be strongly dependent on the concentration of some reactants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature compensation of the oscillation period, or the near-independence of the oscillation period on temperature, is observed at high currents and at lower temperatures. For comparison, the temperature coefficient of 7 Temperature coefficients between 0.67 and 1.80 were obtained by Rábai and co-workers 34 for the classic Bray reaction. Those experiments were carried out in batch, within a temperature interval of 10°C, and the q 10 values were found to be strongly dependent on the concentration of some reactants.…”
Section: Resultsmentioning
confidence: 99%
“…3 From the purely chemical side, the increase of oscillation amplitude with temperature, as suggested by Lakin-Thomas et al, 44 has been observed in the temperature-compensated hydrogen peroxideiodate ion chemical system (the Bray reaction) in batch. 34 Pittendrigh et al 46 studied different aspects of the amplitude of Drosophila circadian pacemaker and observed that, unlike its period, the amplitude of the pacemaker is strongly temperature dependent. The results reported for Drosophila 46 differ from those reported for Neurospora 44 in terms of the temperature dependence of the oscillation amplitude: a temperature rise results in an amplitude decrease in the former case and in an amplitude increase in the latter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 1957, Hastings and Sweeney suggested that in biological clocks such temperature compensation may occur as the result of opposing reactions within the metabolic network [11]. Later kinetic analysis of the problem [12] reached essentially the same conclusion, and predictions of the theory have been tested by experiments using Neurospora 's circadian clock [13] and chemical oscillators [14,15].…”
mentioning
confidence: 99%
“…This apparently simple chemical reaction is a good example of a nonlinear dynamical system in which various non-equilibrium phenomena have been observed experimentally and by theoretical analysis of model mechanisms. However, most often, these studies have focused on the examination of BL properties in a batch reactor 1 [4][5][6][7][8][9][10][11][12][13][14][15][16][17], whereas there is still a relatively small number of investigations that examine BL dynamical properties and underlying molecular mechanisms in an open reactor, i.e. a continuous stirred tank reactor (CSTR) [12,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%